Scorpiops zhui sp. n., a new species of Scorpiops Peters, 1861 from Chongqing, China (Scorpiones: Scorpiopidae) - Lv, He-Yu; Lourenço, Wilson R.; Di, Zhi-Yong (Zootaxa, 2023)
A new species of Scorpiops Peters, 1861 is described from Wuxi and Wushan County, Chongqing City, China. The new species is mainly characterized by a moderate size, in relation to the other species of genus, with dark reddish-brown to reddish-black coloration; 15–17 (usually 17) external trichobothria (5 eb, 1–2 esb, 1–2 em, 4 est, 4 et), 8–11 (usually 10) ventral trichobothria in the pedipalp patella and 4–5 (usually 5) ventral trichobothria on chela; pedipalp chela fingers are scalloped in males and nearly straight in females. With the present description the number of known species of Scorpiops recorded from China is raised to 33.